Sooner or Later: Timing of Monetary Policy with Heterogeneous Risk-Taking - Choi, Dong Beom; Eisenbach, Thomas M.; Yorulmazer, Tanju (American Economic Review, 2016)
We analyze the effects and interactions of monetary policy tools that differ in terms of their timing and their targeting. In a model with heterogeneous agents, more productive agents endogenously expose themselves to higher interim liquidity risk by borrowing and investing more. Two inefficiencies impair the transmission of monetary policy: an investment- and a hoarding inefficiency. Heterogeneous agents respond disparately to ex-ante, conventional and ex-post, unconventional monetary policy. However, we show that the two policies are equivalent due to the endogeneity of hoarding. In contrast, targeted interventions such as discount-window lending can alleviate both inefficiencies at the same time.